Integrated Management of Non-Native Plants in Natural Areas of Florida - Stephen F. Enloe; Kenneth Langeland; Jason A. Ferrell; Brent A. Sellers; Gregory Macdonald (EDIS)
While natural areas are conservation lands that have been set aside for the purpose of preserving (or restoring) native plant and animal communities, they do require active management. One of the greatest management issues in natural areas is invasive plants. This 35-page publication provides land managers in Florida with current methods used to manage non-native plants. Written by Stephen F. Enloe, Ken Langeland, Jason Ferrell, Brent Sellers, and Greg MacDonald, and published by the UF/IFAS Agronomy Department, revised July 2018. http://edis.ifas.ufl.edu/wg209